Deficiency of the myogenic factor MyoD causes a perinatally lethal fetal akinesia. Issue 4 (5th January 2016) - Watson, Christopher M; Crinnion, Laura A; Murphy, Helen; Newbould, Melanie; Harrison, Sally M; Lascelles, Carolina; Antanaviciute, Agne; Carr, Ian M; Sheridan, Eamonn; Bonthron, David T; Smith, Audrey
Abstract : Background: Lethal fetal akinesia deformation sequence (FADS) describes a clinically and genetically heterogeneous phenotype that includes fetal akinesia, intrauterine growth retardation, arthrogryposis and developmental anomalies. Affected babies die as a result of pulmonary hypoplasia. We aimed to identify the underlying genetic cause of this disorder in a family in which there were three affected individuals from two sibships. Methods: Autosomal-recessive inheritance was suggested by a family history of consanguinity and by recurrence of the phenotype between the two sibships. We performed exome sequencing of the affected individuals and their unaffected mother, followed by autozygosity mapping and variant filtering to identify the causative gene. Results: Five autozygous regions were identified, spanning 31.7 Mb of genomic sequence and including 211 genes. Using standard variant filtering criteria, we excluded all variants as being the likely pathogenic cause, apart from a single novel nonsense mutation, c.188C>A p.(Ser63*) (NM_002478.4), in MYOD1 . This gene encodes an extensively studied transcription factor involved in muscle development, which has nonetheless not hitherto been associated with a hereditary human disease phenotype. Conclusions: We provide the first description of a human phenotype that appears to result from MYOD1 mutation. The presentation with FADS is consistent with a large body of data demonstrating that in the mouse, MyoD is a major controller of precursor cell commitment to the myogenic differentiation programme.